1067 плиз даю 20 баллов

3
Ответов - 1
Вопрос задал ученик
Категории: Алгебра

Ответы


Гость
(a(a+2b)+b^{2})=a^{2}+2ab+b^{2}=(a+b)^{2}\\
(a(a-2b)+b^{2})=a^{2}-2ab+b^{2}=(a-b)^{2}\\
((a^{2}-b^{2})^{2}+4a^{2}b^{2})=a^{4}+4a^{2}b^{2}+b^{4}=(a^{2}+b^{2})^{2}
 (a+b)^{2}*(a-b)^{2}*(a^{2}+b^{2})^{2}=(a^{2}-b^{2})(a^{2}-b^{2})(a^{2}+b^{2})(a^{2}+b^{2})=(a^{4}-b^{4})(a^{4}-b^{4})=(a^{4}-b^{4})^{2}

Добавить ответ
Похожие вопросы
Топ Комментарии Архив
«    Ноябрь 2020    »
ПнВтСрЧтПтСбВс
 1
2345678
9101112131415
16171819202122
23242526272829
30 
Теги